Functional status of pediatric patients after extracorporeal membrane oxygenation: A five-year single-center study - Yuhang, Yang; Ni, Yang; Tiening, Zhang; Lijie, Wang; Wei, Xu; Chunfeng, Liu (Frontiers in Pediatrics, 2022)
Objective: Extracorporeal membrane oxygenation (ECMO) is a widely used treatment for circulatory and pulmonary support in newborns and young children. We aimed to determine the incidence of new morbidities, prognoses, and follow-up data of survivors treated with ECMO in pediatric intensive care units (PICU) using the Functional Status Scale (FSS). Methods: We retrospectively collected and analyzed clinical data of patients in the PICU who received ECMO from January 2016 to January 2020. Clinical and functional outcomes were assessed at admission and discharge using the FSS. Twenty-seven patients aged between 1 month and 14 years who received ECMO in the PICU were included. Fifty-two percent were male, and the median age was 36 months (interquartile range, 21–114 months). The patients were admitted for fulminant myocarditis (n = 13), acute respiratory distress syndrome (n = 11), and septic shock (n = 3). Results: Of the 27 patients who received ECMO, 9 (33%) died, whereas 18 survived until discharge. Among the 18 survivors, 12 (44%) had improved conditions and 6 (23%) discontinued treatment and left the hospital; furthermore, of the survivors who were discharged 9 (50%), 7 (39%), 6 (33%), 5 (27%), 1 (6%), and 1 (6%) developed lower extremity deep vein thrombosis, jugular vein thrombosis, acute kidney injury, intracranial hemorrhage and cerebral infarction, pulmonary embolism, and peripheral nerve injury, respectively. Of the 12 patients who survived through 1 year after discharge, 5 (42%) recovered completely, whereas 7 (58%) showed mild to moderate communication and motor dysfunction. The overall survival rate after discharge was 67% (18/27) and 44% (12/27) at 1 year after discharge. Additionally, the incidence of new morbidity after ECMO was 33% (6/18). Conclusions: This study reviewed a single-center experience using FSS for ECMO treatment in a PICU. The patients’ original conditions included fulminant myocarditis, ARDS and septic shock. Short-term survival rate and 1 year survival rate of ECMO patients were 67% and 44% respectively. Approximately one-third of the patients developed new morbidities after ECMO treatment. New dysfunctions increased the risk of death and led to worsening of the functional state. Thus, new dysfunctions may affect the long-term survival outcomes.